Synthesis, physicochemical and biological properties of 6-S- and 6-N-substituted 3-R-2H-[l,2,4]triazino[2,3-c]quinazolin-2-ones - Voskoboynik, O. Yu.; Воскобойнік, Олексій Юрійович (Днепропетровск, 2015)
The present article describes the synthesis and biological activity of series of 6-S- and 6-N-substituted 3-R-2H-[l,2,4]triazino[2,3-c]quinazolin-2-ones. It is shown that 3-R-2H-[l,2,4]triazino[2,3-c]quinazoline-2,6(7H)-diones cannot be used as starting materials for the synthesis of the target compounds, whereas the modification of potassium 3-R-2-oxo-2H-[l,2,4]triazino[2,3-c]quinazolin-6-thiolates provides such an opportunity. The individuality of the synthesized compounds is proved by liquid chromatography-mass spectrometry and their structures by 'H NMR, l3C NMR and mass spectroscopy. The characteristic signals in 'H NMR, l3C NMR - spectra are described; the features of molecule fragmentation under electron impact are elucidated. The anticancer activity according to National Cancer Institute (USA) protocol is evaluated for some of the obtained compounds. The results of anticancer activity allow identifying a compound, which is capable of inhibiting the growth of ovarian cancer cells OVCAR-4 at 61.64%. The results of microbiological screening demonstrate that the synthesized compounds were inactive relative to E. Coli, show a moderate activity against P. aeruginosa and show very encouraging results in the study of antimicrobial activity against S. aureus and antifungal activity against C. albicans. The prospect of further research aimed at creating novel anticancer, antibacterial and antifungal agents based on the compounds described is herein discussed.
Keywords: triazines; quinazolines; anticancer activity; antimicrobial activity; atifungal action